2021
DOI: 10.3390/math9212669
|View full text |Cite
|
Sign up to set email alerts
|

A Significant Solar Energy Note on Powell-Eyring Nanofluid with Thermal Jump Conditions: Implementing Cattaneo-Christov Heat Flux Model

Abstract: PTSCs (parabolic trough solar collectors) are widely employed in solar-thermal applications to attain high temperatures. The purpose of this study is to determine how much entropy is created when Powell-Eyring nanofluid (P-ENF) flows across porous media on a horizontal plane under thermal jump circumstances. The flow in PTSC was generated by nonlinear surface stretching, thermal radiation, and Cattaneo-Christov heat flux, which was utilized to compute heat flux in the thermal boundary layer. Using a similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Ahmad et al evaluated a 3D MHD Maxwell nanofluid flow across a slendering exponentially stretching sheet with energy dissipation using the bvp4c method. Abu-Hamdeh et al computed the quantity of entropy generation when Powell–Eyring nanofluid flows over permeable media in a horizontal surface under thermal jump conditions. Some further explanations and applications of fluid flow along an extending substrate have been discoursed in refs .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmad et al evaluated a 3D MHD Maxwell nanofluid flow across a slendering exponentially stretching sheet with energy dissipation using the bvp4c method. Abu-Hamdeh et al computed the quantity of entropy generation when Powell–Eyring nanofluid flows over permeable media in a horizontal surface under thermal jump conditions. Some further explanations and applications of fluid flow along an extending substrate have been discoursed in refs .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ahmad et al 10 evaluated a 3D MHD Maxwell nanofluid flow across a slendering exponentially stretching sheet with energy dissipation using the bvp4c method. Abu-Hamdeh et al 11 During energy transfers, a hybrid nanofluid surpasses conventional fluids such as acetone, water, nanofluids, and acetylene. The capacity to freeze at high temperatures is one of the many thermal features of hybrid nanofluids.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rashidi et al [ 12 ] have examined the homotopy solution of nanofluid over the non-linear stretching permeable sheet. Abu-Hamda et al [ 13 ] have introduced a significant note on solar energy employing Powell Eyring nanofluid considering thermal jump conditions along with the implementation of the Cattaneo-Christov heat flux model. Aouinet et al [ 14 ] have investigated the hydrodynamic flow of nanofluids and turbulent boundary layers over a plate.…”
Section: Introductionmentioning
confidence: 99%
“…They noticed that higher order reactivity improves the heat transfer rate, whereas mass convection boosts concentration. In addition to analyzing the generation of flow in a parabolic trough solar collector through a non-linear stretching surface under the influence of radiation and Cattaneo–Christov heat flux, Abu-Hamdeh et al [ 59 ] determined the entropy generation in a Powell–Eyring nanofluid across a porous surface. They observed that the generation of entropy is inversely related to thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%